2012
DOI: 10.1590/s1516-44462012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and negative early life events in university students

Abstract: University students with high levels of social anxiety presented higher prevalence of negative early life events. Thus, childhood family violence could be a risk factor for social anxiety in such a population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
1
15
0
4
Order By: Relevance
“…This finding suggests that in this sample, childhood traumas (major ALE, physical, sexual, emotional, and total) are not significantly different in individuals with PTSD and SAD with moderate/severe EDT. Previous studies have found that physical abuse [10,12,13], sexual abuse [12][13][14][15][16][17][18], emotional abuse [19][20][21][22][23], as well as other childhood adversities [24,25] are linked to the development of both PTSD and SAD. Childhood emotional abuse has been found to correlate more strongly with a diagnosis of social anxiety than either physical or sexual abuse [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that in this sample, childhood traumas (major ALE, physical, sexual, emotional, and total) are not significantly different in individuals with PTSD and SAD with moderate/severe EDT. Previous studies have found that physical abuse [10,12,13], sexual abuse [12][13][14][15][16][17][18], emotional abuse [19][20][21][22][23], as well as other childhood adversities [24,25] are linked to the development of both PTSD and SAD. Childhood emotional abuse has been found to correlate more strongly with a diagnosis of social anxiety than either physical or sexual abuse [20].…”
Section: Resultsmentioning
confidence: 99%
“…Afifi et al in 2009 found that a combination of childhood abuse and parental divorce significantly increased the likelihood of a diagnosis of lifetime PTSD in adulthood [24]. Binelli et al in 2012 found only one significant positive correlation between family violence and SAD, although the assessment of childhood trauma was based on five closed questions (yes/no) relating to five childhood adversities, namely, the loss of someone close, emotional abuse, physical abuse, family violence, and sexual abuse [25].…”
Section: Emotional and Other Abuse In Ptsd And Sadmentioning
confidence: 99%
See 1 more Smart Citation
“…Afifi et al in 2009 found that a combination of childhood abuse and parental divorce significantly increased the likelihood of a diagnosis of lifetime PTSD in adulthood [24]. Binelli et al in 2012 found only one significant positive correlation between family violence and SAD, although the assessment of childhood trauma was based on five closed questions (yes/no) relating to five childhood adversities, namely, the loss of someone close, emotional abuse, physical abuse, family violence, and sexual abuse [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde insanların yaklaşık %25'i yaşamının bir döneminde ruhsal sorunlarla karşılaşmaktadır. Son yıllarda yetişkinlerde giderek artan ruhsal sorunların çocukluk veya gençlik dönemindeki olumsuz yaşam olaylarının neden olduğu belirtilmektedir (Binelli, Ortiz, Muniz ve ark., 2012). İyi bir ruh sağlığının temeli çocukluğun ve ergenliğin ilk yıllarında atılır.…”
Section: üNiversite öğRencilerinin Ruhsal Sağlık Durumlarıunclassified